Pengetahuan dan Pengamalan Thaharah Siswa dalam Menjaga Kebersihan dan Kesehatan Era Pandemi Covid-19 di Madrasah - Nur Ainun Nasution (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
The practice of taharah requires Muslims to prevent the transmission of Covid-19. This study aims to analyze the knowledge and practice of students' taharah in the Covid-19 pandemic era. The method used is descriptive qualitative. Among the students' knowledge is knowing the meaning of thaharah (istinja', ablution, tayamum), taharah procedures, thaharah etiquette, thaharah law, sunnah-sunnah thaharah and the meaning of thaharah in a broad sense by maintaining cleanliness and health, especially in the era of the Covid-19 pandemic. The practice of thaharah for students in the era of the covid-19 pandemic, such as routinely brushing their teeth and ablution before going to bed, a small number of students performing ablution outside prayer times, regularizing clean Fridays, cutting nails every Friday and maintaining cleanliness and health through the practice of thaharah. Islam considers cleanliness as a civilization and worship. Therefore, cleanliness is part of the daily life of a Muslim.